A new hypofractionated schedule of weekly irradiation for basal cell carcinoma of the head and neck skin area in elderly patients. Issue 3 (6th August 2013) - Kouloulias, Vassilis; Papadavid, Evaggelia; Mosa, Eutyxia; Platoni, Kalliopi; Papadopoulos, Othon; Rigopoulos, Dimitrios; Georgakopoulos, John; Beli, Ivelina; Karantonis, Fotios; Castana, Ourania; Dalamaga, Maria; Kelekis, Nikolaos
Abstract The effectiveness of radiotherapy in patients with basal cell carcinoma (BCC) has been already reported in the literature. However, there is little information about the irradiation of BCC in elderly patients, especially due to the low conformity of them to daily irradiation. Thirty‐eight retrospectively selected elderly patients (78 years as median age) diagnosed with skin BCC of the head and neck area were treated with five weekly fractions of 600 cGy by three‐dimensional conformal radiotherapy (3DCRT) as an adjuvant treatment. The primary endpoint was the relapse free survival. Acute toxicity, as secondary endpoint, was assessed according to EORTC/RTOG criteria. Among our patients, there were only three local recurrences at 15, 32 and 38 months post‐3DCRT. There was no severe toxicity, while only 10 out of 38 patients presented grade II/III skin toxicity. Our proposed irradiation schedule seems effective in terms of local control and acute toxicity and could be an alternative scheme for elderly patients unfit for daily irradiation.